HIV, cancer, and coping: The cumulative burden of a cancer diagnosis among people living with HIV. Issue 6 (2nd November 2021) - Knettel, Brandon; Corrigan, Kelsey; Cherenack, Emily; Ho, Noelani; Carr, Stuart; Cahill, Joan; Chino, Junzo; Ubel, Peter; Watt, Melissa; Suneja, Gita
Abstract: Objectives: People living with HIV (PLWH) have increased risk for cancer and worse cancer-specific survival. We explored the emotional burden of cancer and HIV as a potential driver of cancer mortality. Research Approach: Semi-structured qualitative interviews with PLWH and cancer. Participants: 27 PLWH who had either completed cancer treatment, were currently undergoing treatment, or experienced challenges in completing treatment. Methodological Approach: An inductive qualitative approach using the constant comparative method. Findings: Participants drew strong parallels between being diagnosed with HIV and cancer. Many described HIV-related stigma that hindered social support. Cancer treatment side effects were a major challenge, impacting treatment adherence for both cancer and HIV. Implications for Psychosocial Providers: There is a need for convenient, affordable, and visible services to support PLHIV as they navigate cancer care. Services should be tailored to the unique needs of this population by addressing HIV-related stigma, building social support, and fostering resilience.